Consensus on consensus: a synthesis of consensus estimates on human-caused global warming. (13th April 2016) - Cook, John; Oreskes, Naomi; Doran, Peter T; Anderegg, William R L; Verheggen, Bart; Maibach, Ed W; Carlton, J Stuart; Lewandowsky, Stephan; Skuce, Andrew G; Green, Sarah A; Nuccitelli, Dana; Jacobs, Peter; et al.
Abstract: The consensus that humans are causing recent global warming is shared by 90%–100% of publishing climate scientists according to six independent studies by co-authors of this paper. Those results are consistent with the 97% consensus reported by Cook et al ( Environ. Res. Lett .8 024024 ) based on 11 944 abstracts of research papers, of which 4014 took a position on the cause of recent global warming. A survey of authors of those papers ( N = 2412 papers) also supported a 97% consensus. Tol (2016 Environ. Res. Lett. 11 048001 ) comes to a different conclusion using results from surveys of non-experts such as economic geologists and a self-selected group of those who reject the consensus. We demonstrate that this outcome is not unexpected because the level of consensus correlates with expertise in climate science. At one point, Tol also reduces the apparent consensus by assuming that abstracts that do not explicitly state the cause of global warming ('no position') represent non-endorsement, an approach that if applied elsewhere would reject consensus on well-established theories such as plate tectonics. We examine the available studies and conclude that the finding of 97% consensus in published climate research is robust and consistent with other surveys of climate scientists and peer-reviewed studies.